The Position of Metaverse Land Assets from the Perspective of Ownership in the Civil Law - Juddin, Muhamad Faiz (Riwayat: Educational Journal of History and Humanities, 2025)
Land assets in the virtual world of the metaverse have become popular and are considered to have high investment potential. In Indonesia, virtual land as an asset is a new object in the law of objects whose provisions have not been regulated in positive law. This research discusses the concept of ownership of metaverse virtual land assets in the classification of civil law in Indonesia.This research includes normative juridical research using a statutory approach. The legal sources are primary, secondary, and tertiary legal materials. The collection of legal materials is a type of literature study and the analysis uses descriptive analysis techniques. The purpose of this research is to analyze the position of metaverse land assets in the review of ownership in the Civil Code.The position of land asset ownership in the metaverse world in the Civil Code system can be analyzed with the provisions of Article 499 of the Civil Code. According to the provisions, goods are every object that can be attached to a right and can be recognized as property rights. The results show that metaverse land assets are included in objects. This digital land asset is included in this intangible object has been regulated in the Civil Code. Metaverse land assets can be attached to property rights to objects. This is because metaverse land assets are included in the category of objects and attached to property rights. Property rights are regulated in article 570 of the Civil Code. A person can take the useful value or sell it from the land assets he owns in the metaverse.